1987
DOI: 10.1149/1.2100733
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ion Implantation to the Study of Electrocatalysis: I . Chlorine Evolution at Ru‐Implanted Titanium Electrodes

Abstract: Ru-implanted titanium near-surface alloys were generated by ion implantation, characterized (Ru concentration/ depth profiles) by Rutherford backscattering, and subsequently anodically oxidized to form electrocatalytically active RuxTil_xOJTi electrodes. The electrochemical behavior of the metallic-like electrodes was investigated in acidic chloride, perchlorate, and sulfate media. A correlation between the rate of the C12 evolution reaction and the Ru-implant profiles established that the reaction is first or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…Electrocatalytic studies in the liquid phase have been performed by Schultze et al [47,48], Kelly et al [59] and Wolf et al [49,60,61].…”
Section: (Electro) Catalytic Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrocatalytic studies in the liquid phase have been performed by Schultze et al [47,48], Kelly et al [59] and Wolf et al [49,60,61].…”
Section: (Electro) Catalytic Reactionsmentioning
confidence: 99%
“…Metallic conducting RuxTil-xO2 layers could be prepared by ion implantation of Ru in Ti metal electrodes and subsequent anodic oxidation [59]. Ion implantation was chosen to prepare those layers in order to circumvent the lateral inhomogeneous nature of conventionally prepared RuxTil_xO2 electrodes.…”
Section: (Electro) Catalytic Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…From recent theoretical studies, [ 9b,14 ] three potential reaction mechanisms for the CER have been well described according to the indirect experimental results of Tafel slopes and reaction orders. [ 15 ] The possible rate‐determining steps (RDS) include the Volmer–Tafel reaction (Equation ()), [ 16 ] Volmer–Heyvrosky reaction (Equation ()), [ 17 ] and Khrishtalik reaction (Equation ()). [ 18 ] Herein, * is an active site, which may be the metal atom or surface oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…One such project involves continuously modifying the electrochemical properties of metal oxide electrodes by doping them with small amounts of impurities metal ions, such as Bi or Sb. It was reported that electrocatalysis could be studied by ion implantation (105). Some interesting studies in electrocatalysis can be done with the ICP-MS ion implantation system because mixtures of different elements can be deposited easily in any desired stoichiometry by introducing a multielement sample into the plasma.…”
Section: Purity Of Ion Depositionmentioning
confidence: 99%